Creativity in Higher Education: The Effect of Personality on Students’ Creative Thinking Skills - Aziz, Rahmat (Thinking Skills and Creativity Journal, 2023)
Creative thinking is an essential skill to be developed in college students. The importance of these skills is not in line with the existing student creativity in higher education. Several studies on students show low levels of these skills. A creative personality is a factor that influences these skills. This study aims to test the influence of creative personality on creative thinking skills. The research uses a quantitative approach with associative design. The research subjects were 90 (ninety) students who were randomly selected by considering the proportion of three state universities in East Java. Data were obtained by measuring creative personality and creative thinking skills through the creative personality scale and creative thinking test. The data were analyzed through regression analysis techniques. Testing is performed simultaneously and partially. The results show that a creative personality affects creative thinking skills. Perseverance is the most dominant factor in influencing students' creative thinking skills. The results of this study imply that the development of students’ creative thinking should be in line with the development of their creative personality.